SOCIO ECONOMIC PROBLEMS OF IT WOMEN PROFESSIONALS IN KERALA - GRACE VARGHESE (ZENITH International Journal of Multidisciplinary Research, 2015)
Today, IT professionals are the most envied people in Kerala. They are envied because of the high pay-scale, glamour and great employment opportunities, associated with IT professional. IT has become the career option for many young educated Indians, for whom it offers salaries unknown in other sectors and an opportunity to live and work outside India. Software engineers, BPO workers and others employed in IT related occupations constitute a new kind of workforce. The IT women professionals face certain problems which affect their family, self and social life, which requires special attention today. In this study mention social economic life of IT professionals.